Biocompatibility assessments of electrospun polycaprolactone scaffolds with hyaluronic acid and/or gelatin surface modification in cultured human exfoliated deciduous cells. - Linsuwanont, Panlapa; Dechkunakorn, Surachai; Anuwongnukrohn, Niwat; Sritanaudomchai, Hathaitip; Tangjit, Nathaphon (Mahidol Dental Journal, 2021)
Objective: The aim of this study was to evaluate the biocompatibility of newly fabricated electrospun Polycaprolactone (PCL) scaffolds with Hyaluronic acid (HA), Gelatin (GE) or HA-GE surface modifications. Material and Methods: The electrospun PCL scaffolds were fabricated by an electrospinning technique then they were surface modified by HA, GE and both HA and GE. Biocompatibility assessments were performed using the MTT and Scratch assays. Confocal fluorescent microscopy was used to examine cell morphology and cell distribution on the scaffolds. Results: The MTT assays indicated that all groups had a high cell viability percentage ranging from 77.76-96.26%, except for the negative control (40%). Among the electrospun PCL scaffolds, the HA-GE-PCL group displayed a significantly lower cell viability. The migrated cell number significantly increased at 12 and 24 h in all groups. At 24 h, the HA-GE-PCL and Commercial PCL (COM-PCL) groups demonstrated higher cell migration. The confocal fluorescent microscopy illustrated that the cells distributed across the electrospun PCL fibers, whereas the cells accumulated along the edge of the mesh in the COM- PCL group. Conclusion: In general, surface modification with HA, GE, or HA-GE on electrospun PCL scaffolds demonstrated high biocompatibility and promoted cell adhesion to the mesh surface.